NONINVASIVE BRAIN STIMULATION IN TRAUMATIC BRAIN INJURY - Demirtas-Tatlidede, Asli (2012)
Brain stimulation techniques have evolved in the last few decades with more novel methods capable of painless, noninvasive brain stimulation. While the number of clinical trials employing noninvasive brain stimulation continues to increase in a variety of medication-resistant neurological and psychiatric diseases, studies evaluating their diagnostic and therapeutic potential in traumatic brain injury (TBI) are largely lacking. This review introduces different techniques of noninvasive brain stimulation, which may find potential use in TBI. We cover transcranial magnetic stimulation (TMS), transcranial direct current stimulation (tDCS), low-level laser therapy (LLLT) and transcranial doppler sonography (TCD) techniques. We provide a brief overview of studies to date, discuss possible mechanisms of action, and raise a number of considerations when thinking about translating these methods to clinical use.